Molding Method of Polymethylmethacrylate Microstructures via Laser Melting - Tan, W.S.; Zhou, J.Z.; Huang, S.; Zhu, W.L. (Asian Journal of Chemistry, 2014)
In order to meet the processing requirements for multiscaled, intricately shaped and high-precision polymer microstructures, this paper presented a molding method based on laser melting and also designed and developed the experimental devices. With CO2 laser radiation, experiments of microstructure molding on PMMA substrates were conducted. By establishing theoretical models and software simulations, this research analyzed specimen temperature changes in the laser scanning process and carried out an orthogonal experiment to analyze the effects of processing parameters on parts quality. Results show that effects of processing parameters on parts quality are as follows: Laser power plays a decisive role in the repetition accuracy. The influencing results of scanning times were also significant, followed by mold temperature and compaction pressure. Optimized technological parameters, such as a laser beam diameter of 20 mm, scanning velocity of 15 mm/s, laser power of 2.7 W, scanning time of 18 s, compaction pressure of 100 N and a mold temperature of 70 ºC, were adopted to obtain molds with high repetition accuracy and a microstructure dimensional deviation of less than 1 μm.